The Effect Of Concentration And Type Of Soaking Solution (Phosphate And Non-Phosphate) On Physical-Sensory Quality Of Frozen Vannamei Shrimp - Annis Mulyani; Agung Dwi; Desiana Nuriza Putri; Noor Harini (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Frozen vaname shrimp is one of the leading export products from the Indonesian fishing industry sector. Soaking is an important step in the frozen shrimp processing chain to increase the yield and quality of the final product. This study aims to determine the effect of adding additives (STPP and Turbo) at various concentrations in soaking shrimp on the physical-sensory quality of frozen white vaname shrimp. This study used factorial RAK with factors I: (1) STPP 3%; (2) STPP 5%, and factor II: (1) Turbo 2%; (2) Turbo 4%. The quality parameters observed included physical quality (net recovery, step loss, drip loss, cooking loss, increase in check size) and sensory quality (appearance, smell, taste, texture). Data were analyzed by analysis of variance (ANOVA) and DMRT follow-up test (for physical quality), and Dunnet follow-up test (for sensory quality) at 95% confidence level. Descriptive statistical analysis was used for data that did not meet the ANOVA test. The results showed that the addition of STPP and Turbo at various concentrations had no significant effect (α> 0.05) on net recovery, step loss, cooking loss, and product sensory quality. The percentage of stage losses is influenced by the net recovery and gross recovery of shrimp, and all the treatments tested were acceptable to all panelists.